Religion, the Royal Society and the rise of science - Harrison, P (Routledge, 2008)
Accounts of the role of religion in the rise of modern science often focus on the way in which religion provided the intellectual foundations for scientific enquiry, motivated particular individuals, or provided the substantive content of approaches to nature. These relate to the origins of science and assume that, once established, modern science becomes self-justifying. However, seventeenth-century criticisms of science— attacks on the Royal Society being one example—suggest that science remained a marginal and precarious activity for some time. The rise of science to cultural prominence in the eighteenth and nineteenth centuries was possible only because science was eventually able to establish itself as religiously useful enterprise. Religion thus played a key role not only in the origins of modern science, but in providing the ongoing social sanctions that ensured its persistence and rise to prominence.